Taxonomic studies on the genus Hydrocotyle (Apiales) from China: The distribution and morphology of H. chiangdaoensis, with H. calcicola reduced to a synonym - Jun Wen; Jun-Wen Zhu; Ren-Bin Zhu; Chun-Feng Song (PhytoKeys)
Based on observations of living plants of Hydrocotyle calcicola in the field, together with examination of herbarium specimens and descriptions of both H. calcicola and H. chiangdaoensis (including type material), we demonstrated that H. calcicola is a synonym of H. chiangdaoensis. The species was previously compared with H. sibthorpioides; our phylogenetic analysis revealed that H. chiangdaoensis and H. sibthorpioides belong to different lineages, the former being closely related to the larger-leaved clade.